Characterization of key aroma components of jasmine tea with diverse aroma types: Focus on jasmine tea scented with multipetal jasmine - Yuan Chen; Huimin An; Yiwen Huang; Youcang Jiang; Jiaqi Ying; Sirui Wang; Chunniu Li; Zhaoyang Bu; Xianmin Li; Yuelan Pang; Zhusheng Liu; Shi Li; et al. (Food Chemistry: X)
In this study, the aroma characteristics of jasmine tea (JT) scented by three kinds of multipetal jasmine, Xiangfei 2, 4 and 11 were investigated with common double-petal jasmine as control. Compared with the strong floral aroma of double-petal jasmine tea (TS), the JT scented with Xiangfei 2 (TC) showed fresher aroma, the JT scented with Xiangfei 11 (TB) exhibited sweeter aroma, while the overall aroma of JT scented by Xiangfei 4 (TA) was overall lower. Among them, Benzoic acid, 2-hydroxyl-, ethyl ester contributed to TB's sweet note, 3-Hexen-1-ol, benzoate, (Z) - and Methyl salicylate were related to the fresh aroma of TC, Linalool, Methyl anthranilate, 4-Hexen-1-ol, acetate and Benzyl alcohol were linked to TS's floral aroma. Molecular docking identified hydrogen bonding and hydrophobic interactions as key drivers for aroma compounds binding to olfactory receptors, and molecular dynamics simulations (MDs) validated the stability of these interactions. This study provides a theoretical basis for the application of multipetal jasmine in JT processing.